Robotic Insertion Aid for Self-Coiling Cochlear Implants. Issue 1 (2016) - Ajieren, Hans; Reit, Radu; Lee, Roxanne; Pham, Tiffany; Shao, Dongmei; Lee, Kenneth; Voit, Walter
ABSTRACT: This study investigates the use of shape memory polymers (SMPs) as a substrate for a self-coiling cochlear implant electrode array and investigates the self-coiling ability of a sham probe micromachined atop such a substrate. Through the use of a self-coiling cochlear implant, the capability to avoid contact with the tissue of the cochlear duct is investigated via the insertion of a dummy device into a model cochlea heated to an ambient 34 °C. Finally, a prototype straightening and insertion tool is developed for automated retraction and locking of the coiled shape into a bar geometry. Preliminary demonstration of the deployment of self-coiling cochlear implants is shown and paves the way for future studies focused on using histological analysis of the cochlear wall tissue to compare the degree of trauma resulting from linear cochlear implant arrays versus the self-coiling, non-contact probes demonstrated herein.